Nitrogen-doped silicon: Mechanical, transport and electrical properties - Murphy, J; Alpass, C; Giannattasio, A; Senkader, S; Emiroglu, D; Evans-Freeman, J; Falster, R; Wilshaw, P (2006)
A novel dislocation locking technique is used to study the behaviour of nitrogen in float-zone silicon (FZ-Si). Specimens containing well-defined arrays of dislocation half-loops are subjected to isothermal anneals of controlled duration, during which nitrogen diffuses to the dislocations. The stress required to bring about dislocation motion is then measured. From measuring this unlocking stress as a function of annealing time and temperature it is possible to deduce information on nitrogen transport and nitrogen-dislocation interactions. In this paper, the results obtained by using the dislocation locking technique are reviewed. Furthermore, deep-level transient spectroscopy (DLTS) and high-resolution DLTS (HR-DLTS) are applied to nitrogen-doped silicon. A deep-level with an emission enthalpy of approximately 0.50eV and a concentration of order 1011cm-3 was found in n-type nitrogen-doped FZ-Si and n-type nitrogen-doped neutron transmutation doped FZ-Si. No additional deep-levels with a concentration of greater than 6 × 1010cm-3 were found in either material. No deep-levels were found in p-type nitrogen-doped Czochralski silicon (Cz-Si), for which the detection limit was approximately 1012cm-3. copyright The Electrochemical Society.